Becouse k and n are 'neighbours' so their sum are 180
so k=180-42=138
If the original side length is "s" and the original slant height is "h", the original surface area is
.. S = (base area) +(lateral area)
.. S = s² +(1/2)*(4s)*h
.. S = s(s +2h)
Now, if we make these replacements: s ⇒ 3s, h ⇒ h/5, we have
.. S' = (3s)(3s +2h/5)
.. S' = 9s² +(6/5)s*h . . . . . . . the formula for the modified area (in terms of original dimensions)
_____
Of course, in terms of the modified dimensions, the formula is the same:
.. S' = s'(s' +2h')
Simplifying
j = (2j + 3)
Reorder the terms:
j = (3 + 2j)
Remove parenthesis around (3 + 2j)
j = 3 + 2j
Solving
j = 3 + 2j
Solving for variable 'j'.
Move all terms containing j to the left, all other terms to the right.
Add '-2j' to each side of the equation.
j + -2j = 3 + 2j + -2j
Combine like terms: j + -2j = -1j
-1j = 3 + 2j + -2j
Combine like terms: 2j + -2j = 0
-1j = 3 + 0
-1j = 3
Divide each side by '-1'.
j = -3
Simplifying
j = -3
Answer:
1.59&-1.59
Step-by-step explanation:
.53(3)+5=1.59